87.5k views
0 votes
Simplify the expression (2 square root sign 27) - (3 square root sign 32)

1 Answer

5 votes

Answer:


3√(3) - 4√(2)

Explanation:

The expression (2 square root sign 27) - (3 square root sign 32) is
2√(27) - 3√(32).

To simplify, simplify inside the radicals by removing perfect square factors.


√(27) =√(9*3) =3√(3)


√(32) =√(16*2) =4√(2)

The expression becomes
3√(3) - 4√(2).

This cannot be simplified anymore because whats under the radical is not the same.

User Danil Asotsky
by
6.0k points